2001
DOI: 10.3390/60300230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Acridine-based DNA Bis-intercalating Agents

Abstract: Methods for the synthesis of N1, N8-bis(9-acridinyl)-N4-(4-hydroxybenzyl)-spermidine and N1, N7-(hydroxybenzyl)-bis-(3-aminopropyl)amine were investigated. Thus monocyanoethylation of 4-methoxybenzylamine followed by treatment with 4-chlorobutyronitrile gave the dinitrile N-(2-cyanoethyl)-N-(3-cyanopropyl)-4-methoxy-benzylamine. Subsequent in situ reduction with lithium aluminium hydride gave the corresponding diamine. Biscyanoethylation of 4-methoxybenzylamine with 2 mole of acrylonitrile followed by reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Ressalte-se que micromoléculas, como a actinomicina-D, a daunomicina e a adriamicina, também atuam diretamente no DNA, mas por intercalação entre nucleotídios vicinais da fita do DNA, via interações de van der Waals e iônicas. Deste modo, a intercalação interfe nas funções normais do DNA, bloqueando as polimerases e interferindo na síntese de proteínas 78 . Em sua ação natural, estas topoisomerases assentam-se na estrutura do DNA por uma supertorção (dobras) topológica, quando fazem cortes, permitindo que as funções de transcrição, reparação, replicação e estruturação do cromossomo ocorram normalmente.…”
Section: Apoptose Via Inibição Das Topoisomerases I E Iiunclassified
“…Ressalte-se que micromoléculas, como a actinomicina-D, a daunomicina e a adriamicina, também atuam diretamente no DNA, mas por intercalação entre nucleotídios vicinais da fita do DNA, via interações de van der Waals e iônicas. Deste modo, a intercalação interfe nas funções normais do DNA, bloqueando as polimerases e interferindo na síntese de proteínas 78 . Em sua ação natural, estas topoisomerases assentam-se na estrutura do DNA por uma supertorção (dobras) topológica, quando fazem cortes, permitindo que as funções de transcrição, reparação, replicação e estruturação do cromossomo ocorram normalmente.…”
Section: Apoptose Via Inibição Das Topoisomerases I E Iiunclassified
“…As was mentioned above, some comprehensive reviews and papers of acridine derivatives have reported anticancer and intercalating properties due to the planar structure of the acridine skeleton (Antonini et al ., ; Brana et al ., ; Cholewinski et al ., ; Demeunynck, ; Galvez‐Peralta et al ., ; Ihmels & Otto, ; Kumar et al ., ; Moloney et al ., ; Murza et al ., ; Neidle & Abraham, ; Pereira et al ., ; Ryan et al ., ; Tsankov et al ., ). The interesting qualities of acridine ureas and thioureas have inspired Kožurkova and her team (Janovec et al ., ; Kožurkova et al ., , ; Sabolova et al ., ; Vantova et al ., ) to examine further potential uses of these new bioactive derivatives.…”
Section: Proflavine Ureas and Thioureas As Novel Acridine Anticancer mentioning
confidence: 99%
“…This chromosomal mutation seems to be related to the ability of proflavine to stabilize DNA-topoisomerase intermediates (Biver et al, 2003;Gurova, 2009;Lang et al, 2013;Wang et al, 2010;Yang et al, 2005). Proflavine is an acridine dye and has been shown (Moloney et al, 2001) to bind directly with nucleic acids; the conjugate of this interaction becomes highly photosensitive. The physicochemical properties of the proflavine moiety permit the use of sensitive spectroscopic techniques to examine the nature of the interactions of the relevant derivatives with DNA (Cholewinski et al, 2011;Moloney et al, 2001;Neidle & Abraham, 1984).…”
Section: Synthesis Of Thioureasmentioning
confidence: 99%
“…Furthermore, cytotoxic modes of action of pyridoacridine alkaloids include DNA-binding properties, topoisomerase (TOPO) inhibition [ 91 ] or the production of reactive oxygen species (ROS) [ 92 93 ]. It was shown that planar iminoquinone moieties and an acridine core are two pharmacophoric motifs inhibiting the proliferation of cancer cells through intercalation into DNA [ 42 , 94 95 ]. Compounds with such a feature can also cleave the DNA double helix or inhibit the action of TOPO [ 42 , 94 95 ].…”
Section: Reviewmentioning
confidence: 99%